Analysis of Bullying Behavior Prevention in Grade V Of SDN 17 Palu - Fajriani Anwar; Yun Ratna Lagandesa; Sisriawan Lapasere; Rizal Rizal; Rangga Putera Boroallo (FKIP - Universitas Riau, 2026)
Bullying remains a common problem in elementary schools and may negatively affect students' psychological, social, and academic development. This study aimed to analyze the forms of bullying behavior and the school's prevention strategies among fifth-grade students at SDN 17 Palu. A qualitative descriptive approach was employed involving one principal, one fifth-grade teacher, and five students selected through purposive sampling. Data were collected through classroom observations and semi-structured interviews and analyzed using the Miles and Huberman interactive model. The findings showed that verbal bullying, particularly mocking classmates by mentioning their parents' names and giving inappropriate nicknames, was the most dominant form, while physical bullying, such as pushing and hitting, occurred less frequently and was often perceived as joking. The school addressed bullying by establishing an anti-bullying team, integrating anti-bullying education into classroom learning, conducting awareness activities, involving parents, and collaborating with the local education office. The study concludes that collaborative and continuous prevention efforts are essential for creating a safe school environment and reducing bullying among elementary school students.